A reflectarray Using a Dielectric Discretized Concave Mirror Based on Electromagnetic Band Gap - Gustavo Maciulis Dip; Fatima Salete Correra (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract This paper presents a reflectarray antenna with an innovative dielectric mirror in the form of a discretized concave reflector. The mirror, manufactured via 3D printing, combines dielectric and air layers, forming an Electromagnetic Band Gap (EBG) that reflects signals to the reflectarray feed antenna within its operating frequency band. A transmission line model was used for EBG parametric analysis, resulting in a simple, fast, and efficient design tool implemented in Octave. A design technique was developed to optimize the position and tilt of each mirror element, aligning reflected signal phases for constructive addition in the antenna's main beam direction. An Octave code implemented this design technique. Additionally, a Python program automated the generation of the dielectric reflector simulation model for Ansys HFSS. A reflectarray antenna is designed to operate in the 10.7 GHz to 12.7 GHz band, using a Yagi-Uda feed and a dielectric reflector made of PLA and air layers. The reflectarray antenna was manufactured and characterized, demonstrating a gain of 19.56 dBi and a half-power beam width of 8.04 degrees at 11.7 GHz at 〖θ〗_0=23° and 〖φ〗_0=0°. Good agreement was obtained between simulated and measured results, validating the design procedure.